The classical pathway of complement - Daha, Mohamed R. (Henry Stewart Talks, 2017)
Three activation pathways of complement, Initiation of the classical pathway, Dose-dependent effects of terminal complement complexes, Hemolytic assays and ELISA for quantification of complement activity, Clearance of self-debris and of immune complexes, Complement deficiency and autoimmunity, Disturbed apoptotic cell processing, Systemic Lupus Erythematosus, Fluid phase and membrane-bound complement regulators